Ex-President of Botswana Ian Khama: Ascents and Reversals in the Political Career of a Former Pilot - PROKOPENKO Liubov Yaroslavovna (Ученые записки Института Африки Российской академии наук)
The article shows the development of the political career of the ex-president of Botswana Ian Khama, a son of the country’s first president Seretse Khama.